A chemotaxis-based explanation of spheroid formation in 3D cultures of breast cancer cells. (21st October 2019) - Bubba, Federica; Pouchol, Camille; Ferrand, Nathalie; Vidal, Guillaume; Almeida, Luis; Perthame, Benoît; Sabbah, Michèle
Highlights: We report new experimental results of breast cancer cells organising in spheroids in 3D hydrogels. Experimental results are presented in detail to describe the dependance on the initially seeded cells and on cell line. We model the observed spheroids as chemotaxis-driven patterns, solutions of a Keller-Segel type system. The analysis of the model reveals a time-dependent instability condition coherent with biological observations. Two-dimensional numerical simulations show a good qualitative match with the experiments. Abstract: Three-dimensional cultures of cells are gaining popularity as an in vitro improvement over 2D Petri dishes. In many such experiments, cells have been found to organize in aggregates. We present new results of three-dimensional in vitro cultures of breast cancer cells exhibiting patterns. Understanding their formation is of particular interest in the context of cancer since metastases have been shown to be created by cells moving in clusters. In this paper, we propose that the main mechanism which leads to the emergence of patterns is chemotaxis, i.e., oriented movement of cells towards high concentration zones of a signal emitted by the cells themselves. Studying a Keller–Segel PDE system to model chemotactical auto-organization of cells, we prove that it admits Turing unstable solutions under a time-dependent condition. This result is illustrated by two-dimensional simulations of the model showing spheroidal patterns. They are qualitatively compared to the biological results and their variability is discussed both theoretically and numerically.